Coralline algae from the Ninniyur Formation (Thanetian) of the auvery Basin, South India - Kishore, S.; Singh, S.K. (Our Nature, 2006)
The Palaeocene sediment of the Tiruchirapalli area show presence of some elements of geniculate and non geniculate coralline algae. Four coralline algal species are recorded from this Formation (Thanetian age). Two of the described species belong to Sporolithon. Of the remaining two, one is assigned to Corallina, while the other one is indeterminate, being referred to the subfamily Melobesioideae because of the absence of diagnostic features. Key words: Coralline Algae, Palaeocene, Ninniyur Formation, Cauvery Basin. doi:10.3126/on.v2i1.316 Our Nature (2004) 2:1-6